Schools as Imagined Communities - Dorn, S. author. aut Link
XI, 217 p.
Keywords: Government forces mean the notion of a 'community' school has become less defined by decisions on core curriculum. This collection explores the extent to which collective notions of school-community relations have prevented citizens from speaking openly about the tensions created where schools are imagined as communities.